Penguatan Tradisi Aswaja An-Nahdliyah - Mukhamat Saini (LPPM IAIN Sorong, 2022)
Abstract: This study reviews the strengthening of the Aswaja An-Nahdliyah tradition; efforts to counter the transnational Islamic movement. Talking about the transnational Islamic movement, it cannot be separated from the desire of the Islamist group. Such as Hizbut Tahrir Indonesia (HTI) and the Muslim Brotherhood (IM) to introduce Islam that really refers to the Qur'an and the Sunnah of the Prophet. The purpose of this study is to describe the transnational Islamic movement. Next, it describes the Aswaja An-Nahdliyah tradition in the context of internal strengthening of the Nahdliyin youth. Then, analyze the impact of strengthening the Aswaja An-Nahdliyah tradition in an effort to ward off transnational movements. This study uses a qualitative phenomenological approach (qualitative phenomenological approarch) which aims to describe the situation or phenomena that occur qualitatively descriptively. Data analysis techniques in this research are data collection, data reduction, data presentation, conclusion and verification. The results of this study are first, the pattern in the transnational Islamic movement is influenced by the transmission and transformation of knowledge, then the piety movement (politic of piety) and political movement. Second, the Aswaja An-Nahdliyah traditions are the pilgrimage to the grave, Yasinan and Tahlilan, Manaqiban and Maulid Nabi, Ruwahan or Nyadran, Istighosah, the tradition of Bulan Suro, Ngapati and Mitoni or Tingkepan, the tradition of the Month of Shafar. Third, in the tradition of Pilgrimage to the Grave, Tawassul teaches the value of humility and tawadlu'. With the Istighatsah tradition, it is able to strengthen Ukhuwah. As for Ukhuwah, which is embedded in Muslims, it will fend off everything that leads to violence that leads to radicalism. When Muslims get used to the Khotmil Qur'an tradition, Muslims will motivate themselves to learn and practice Islamic teachings. So, strengthening the Aswaja An-Nahdliyah tradition is one of the most effective vaccines in an effort to prevent and at the same time fight the infiltration of transnational Islamic movements.